Sources of Financing Knowledge-Based Economy: the Case of Formal, Non-Formal and Informal Education in Poland - Iwona Kowalska (Institute of Economic Research (IER), 2015)
Globalization, negative demographic trends, new sources of knowledge and volatile job market are the determining factors behind the change in approach to the education system in Poland. Formal, non-formal and informal education is the sine qua non of the implementation of a knowledge-based economy in Poland. This process, however, requires an in-depth analysis of the funding of education. So far there have been no Polish publications analyzing the funding of the three aforementioned forms of education. Therefore, the aim of this article is to assess the possibilities to implement knowledge-based economy with regard to the current funding of formal, non-formal and informal education in Poland. The study involved the analysis of national and EU documents on subject and object oriented funding of educational tasks and procedures for determining the amount of funding allocated to these tasks. The analysis showed that the barrier inhibiting the implementation of knowledge-based economy is the lack of legal regulations enabling the implementation of new solutions for financing education in Poland. These solutions involve the effective joint funding from the state budget, local government budgets and private funds (provided by employers and learners). This requires urgent conceptual work and initiating implementation projects in the area of public finance in Poland.
Keywords: G18; H52; I22; 330; finance; education; economy; knowledge; system